Potential of flax fiber reinforced biopolymer composites for cross-arm application in transmission tower: a review - Asyraf, Muhammad Rizal Muhammad; Ishak, Mohamad Ridzwan; Norrrahim, Mohd Nor Faiz; Amir, Abdul Latif; Nurazzi, Norizan Mohd; Ilyas, Rushdan Ahmad; Asrofi, Mochamad; Rafidah, Mazlan; Razman, Muhammad Rizal (Springer, 2022)
Abstract not available.